A Critical Review of Educational Games as a Tool for Strengthening Digital Literacy - Rohmani, Rohmani; Pambudi, Nanda (Future Science / FSH-PH Publications, 2023)
The digital era is an era where knowledge can be easily obtained anytime and anywhere as long as it is connected to the internet network. To be able to access knowledge requires a special skill called digital literacy skill. Digital literacy skills can be developed in various ways, one of which is through game-based learning. The purpose of this study is to identify the development of the use of games in education that has been carried out by previous researchers related to strengthening digital literacy. The method used to collect data is by a systematic review, which is a research method by collecting and summarizing all the best available research on a particular question, using a transparent protocol that can be replicated to find, evaluate, and synthesize relevant research evidence. The results of the study obtained data from the scopus.com database with the keywords educational games in digital literacy learning as many as 189 articles and 13 articles that met the inclusion criteria for analysis. The use of educational games to strengthen digital literacy has been carried out in several countries with different types of games with the scope of increasing digital literacy skills, Collaboration and creativity, Finding Information, Critical Thinking, and Social Understanding.